The 4-Year Experience with Implementation and Routine Use of Pathogen Reduction in a Brazilian Hospital - Roberta Maria Fachini (MDPI AG, 2021)
(1) Background: We reviewed the logistics of the implementation of pathogen reduction (PR) using the INTERCEPT Blood System™ for platelets and the experience with routine use and clinical outcomes in the patient population at the Sírio-Libanês Hospital of São Paulo, Brazil. (2) Methods: Platelet concentrate (PC), including pathogen reduced (PR-PC) production, inventory management, discard rates, blood utilization, and clinical outcomes were analyzed over the 40 months before and after PR implementation. Age distribution and wastage rates were compared over the 10 months before and after approval for PR-PC to be stored for up to seven days. (3) Results: A 100% PR-PC inventory was achieved by increasing double apheresis collections and production of double doses using pools of two single apheresis units. Discard rates decreased from 6% to 3% after PR implementation and further decreased to 1.2% after seven-day storage extension for PR-PCs. The blood utilization remained stable, with no increase in component utilization. A significant decrease in adverse transfusion events was observed after the PR implementation. (4) Conclusion: Our experience demonstrates the feasibility for Brazilian blood centers to achieve a 100% PR-PC inventory. All patients at our hospital received PR-PC and showed no increase in blood component utilization and decreased rates of adverse transfusion reactions.